Colonization of Mars, the red planet: a feasibility study on creating an atmosphere using Martian resources - Wempe, John Michael (Kansas State University, 2019)
Acting under the assumptions of a restored magnetic field and primary utilization of Martian resources, the current conditions on Mars are described with an emphasis on information necessary to terraform and colonize the planet. Perchlorate, sulfate, and nitrate in the Martian regolith were identified as key sources for atmosphere production. These sources were inventoried using information from the National Aeronautics and Space Administration (NASA) and the European Space Agency (ESA). These inventories were compared to the mass needed to create an atmosphere on Mars. These resources were found to yield only 2.76% of the mass needed to terraform the planet. The amount of interior atmosphere for habitation facilities that could be generated was also calculated based on the same mass. With nitrogen as the limiting ingredient for atmosphere, the conversion of 100% of the planet’s nitrate reserves would result in the creation of 7.01E+14 m³ of breathable air, over 200 million Superdome sized facilities, with an excess supply of oxygen available from perchlorate and sulfate reserves. The proposed means of conversion was by the use of bioelectrochemical reactors (BERs) in conjunction with highly specialized bacterial populations. These reactors allow for resource efficient reductions to take place, where electrical current is used as the sole electron donor. The reactions would meet weight constraints for travel but were found to be far too slow for effective use. Based on the reaction rate of 50 mg/L per day from pilot scale research, millions of liters of reactor volume would be needed for effective conversions. Research into faster conversion mechanisms and reactor designs are required for colonization of Mars.
Keywords: Mars; Terraforming; Mars Colonization; Perchlorate; Atmosphere; Space Exploration